2009
DOI: 10.1016/j.jhazmat.2008.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbent materials from paper industry waste materials and their use in Cu(II) removal from water

Abstract: Keywords:Paper industry waste materials Pyrolysis Adsorbent This paper deals with the removal of Cu 2+ from water using adsorbent materials prepared from paper industry waste materials (one de-inking paper sludge and other sludge from virgin pulp mill). Experimental results showed that de-inking paper sludge leads to mesoporous materials (V mic /Vr = 0.13 and 0.14), whereas the sludge from virgin pulp mill produces high microporous adsorbents (V m j C /V T = 0.39 and 0.41). Adsorbent materials were then used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 23 publications
(27 reference statements)
4
39
0
Order By: Relevance
“…Also oxygen functional groups are known to stabilise heavy metals in the biochar surface, particularly (Uchimiya et al, 2011c) for softer acids like Pb +2 and Cu +2 . In addition, Méndez et al (2009) observed that Cu +2 sorption was related to the elevated oxygenated surface groups and also with high average pore diameter, elevated superficial charge density and Ca +2 and Mg +2 exchange content of biochar. Possibly, sorption mechanisms are highly dependent on soil type and the cations present in both biochar and soil.…”
Section: Mechanism Of Interaction Between Biochar and Heavy Metalsmentioning
confidence: 96%
“…Also oxygen functional groups are known to stabilise heavy metals in the biochar surface, particularly (Uchimiya et al, 2011c) for softer acids like Pb +2 and Cu +2 . In addition, Méndez et al (2009) observed that Cu +2 sorption was related to the elevated oxygenated surface groups and also with high average pore diameter, elevated superficial charge density and Ca +2 and Mg +2 exchange content of biochar. Possibly, sorption mechanisms are highly dependent on soil type and the cations present in both biochar and soil.…”
Section: Mechanism Of Interaction Between Biochar and Heavy Metalsmentioning
confidence: 96%
“…Also oxygen functional groups are noted to have stabilised trace metals in a biochar surface, mostly for softer acids like Cu 2+ and Pb 2+ [67,70]. Furthermore, Cu 2+ adsorption was reported to have related to the higher oxygenated surface groups and also with high average pore diameter, higher superficial charge density and Ca 2+ and Mg 2+ exchange content of the biochar [73].…”
Section: Mechanism Of Interaction Between Biochar and Trace Metalsmentioning
confidence: 99%
“…A growing demand for inexpensive sorption materials capable of meeting the requirements specifications stimulates the development of new ways to obtain sorbents [5]. The most efficient in eco-economic trend of research is the development of new inexpensive effective sorbents based on industrial waste that allows decreasing anthropogenic load on the environment in many directions [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%